Melatonin ameliorates hepatic steatosis by inhibiting NLRP3 inflammasome in db/db mice. (16th August 2021) - Yu, Yongxiang; Chen, Dongru; Zhao, Yuhua; Zhu, Jianjun; Dong, Xiaohui
Introduction: Type 2 diabetes mellitus (T2DM) is commonly accompanied by obesity and non-alcoholic fatty liver disease (NAFLD), yet the mechanism underlying diabetes-related NAFLD is not fully understood. It has been reported that melatonin can regulate glucose and lipid metabolism. This study aims to investigate the actions and mechanisms of melatonin toward the development of diabetes-related NAFLD. Methods: Melatonin (bid, 30 mg/kg/day, i.p. ) was administrated to db/db mice for 8 weeks, while saline was administrated to db/m mice. The metabolic parameters of mice were measured using an automatic biochemistry analyzer. The oxidative stress indexes and mitochondrial membrane potential (MMP) were determined with kits. Pathological assessment in liver tissues was used to analyze the effects of melatonin on hepatic steatosis. The levels of IL-1β and IL-18 were detected with ELISA kits. The mRNA levels of NLRP3 inflammasome were detected using quantitative real-time PCR assay, and protein expressions were estimated using Western blotting assay. Immunofluorescence staining was used to evaluate the caspase-1 expression in the liver. Results: Melatonin treatment significantly reduced blood glucose, serum insulin, body weight, related liver weight, serum lipids, and hepatic enzymes in db/db mice. Melatonin markedly corrected the NAFLD phenotypes, including lipid accumulation, steatohepatitis, fibrosis, and oxidative stress levels. Melatonin significantly improved the MMP level and decreased the serum IL-1β and IL-18 concentrations. The mRNA levels of the NLRP3 inflammasome could also be remarkably reversed by melatonin in the liver tissues. The activation of the NLRP3 inflammasome was also suppressed, evidenced by the downregulated proteins of NLRP3, caspase-1, IL-1β, and IL-18. The enhanced fluorescence intensity of caspase-1 in the liver tissues was also obviously weakened by the melatonin treatment. Conclusion: Our study concluded that melatonin could safeguard against NAFLD by improving hepatic steatosis in db/db mice, and this action could be associated with the regulation of the NLRP3 inflammasome activation.